Evaluation of a training program for community-based end-of-life care of older people toward aging in place: A mixed methods study. (July 2021) - Nagata, Chizuru; Tsutsumi, Masae; Kiyonaga, Asako; Nogaki, Hiroshi
Abstract: Aims: To evaluate a training program that supports community-based service staff in implementing aging-in-place and end-of-life care programs. Background: Globally, as the population ages, the need for end-of-life care has never been greater. Since Japan is facing the issues of a super-aged population sooner than most countries, there is a particularly urgent need to enhance end-of-life care for older people. Most Japan's older people wish to spend their final days at home, however, only 11–13% end their lives at home, while 73% die in hospitals. As part of care system, small-scale community-based service for aging-in-place established across Japan in 2006 managed locally. These are flexible services using home or facility care or both for the individual to live long term at their preferred place. We developed the end-of-life care educational training program to encourage behavioral changes in community-based service staff of various readiness levels. Design: Mixed methods study design. Methods: A pre-post evaluation of knowledge, confidence and attitude toward end-of-life care, combining quantitative and qualitative data from 53 community-based service staff members who participated in the training program from September 2017 to September 2019. Participants were informed of the end-of-life care process using focus group discussions about end-of-life care and completed surveys evaluating the program before, immediately following and three months after the training. We used the four-level Kirkpatrick model as the evaluation indicator. Results: Quantitative analysis results indicated that participants were satisfied with the training program. Their knowledge scores regarding end-of-life care significantly improved; they also experienced confidence gains and changes in attitudes, becoming more approving of end-of-life care. Qualitative data revealed details of participants' satisfaction and what was learned. Through the focus group discussions, they created action plans for implementing end-of-life care programs, which some had accomplished in their local centers by the three-month follow-up. Conclusions: These results suggest that the training program is effective for promoting end-of-life care through community-based services in Japan. Conducting follow-up training could effectively strengthen participants' commitment to end-of-life care at community-based services. Use of the training program is expected to promote services to support aging-in-place. Highlights: Community based end-of-life care for older people with "Aging-in-Place" training can lead to a "good death". This training program focusing on group discussions with participants was effective. Action plans were implemented into end-of-life care through programs. Evaluation of the training program using Kirkpatrick model's four-levels was successful. This program is promoting end-of-life care through community-based services in Japan.